Solving the bi-level problem of a closed optimization of electricity price zone configurations using a genetic algorithm - Tim Felling (University of Duisburg-Essen, House of Energy Markets & Finance, 2019)
The topic of alternative price zone configurations is frequently discussed in Central Western Europe where - so far - national borders coincide with borders of price zones. Reconfiguring these price zones is one option in order to improve congestion management, foster trading across borders of price zones and, thus, to increase welfare. In view of the significant increase in redispatch volumes and costs over the last years due to increasing feed-in from renewable energy sources in conjunction with delayed grid expansion, this topic has gained in importance. To determine these improved price zone configurations for a large-scale system like Central Western Europe, often either configurations based on expert guesses are considered or heuristics using approximate criteria like locational marginal prices are used to obtain price zones through clustering. In contrast, the present paper formulates a bi-level optimization problem of how to determine optimal configurations in terms of system costs and - given the size and nature of the problem - solves it with a specially developed genetic algorithm. Resulting price zone configurations are compared to both exogenously given, expert-based price zone configurations from the Entso-E bidding zone study and endogenously assessed configurations from a hierarchical cluster algorithm. Results show that the genetic algorithm achieves best results in terms of system costs. Moreover, the comparison with solutions from a hierarchical cluster analysis reveals important drawbacks of the latter methodology
Keywords: C38; C61; D47; L5; Q48; 330; price zone configuration; bidding zone configuration; cluster algorithm; genetic algorithm; evolutionary algorithm; locational marginal prices